A Bibliometric Analysis of Problem-Solving Skill and STEM Integration in Education (Scopus Database 2004-2024) - Reny Afifah; Heru Kuswanto; Ayu Mar’ati BN (Jurnal Penelitian Pendidikan IPA, 2025)
Problem solving and STEM integration in education are important in many countries around the world. Problem solving and STEM integration in education can also be applied at various levels. This study aims to describe the development trends of research in the topic, as well as to identify the most relevant and widely cited countries, sources and topics in the related literature. Previous studies have shown that problem solving and STEM integration are mostly applied in secondary schools. In this study, we extracted from the Scopus database to analyze and evaluate the results of scientific publications related to problem solving and STEM integration in education during 2004-2024. The number of publication data that has been filtered is 106 publications, all of which are taken from the Scopus database. The results of the quantitative analysis show that research on problem solving and STEM integration in education has grown rapidly in the last 5 years. The most relevant and most cited country is the USA. Meanwhile, the most relevant source is CBE Life Sciences Education. The research topics are also quite diverse, focusing on several issues: engineering, education, humanism, professional aspect, etc. This research has limitations, because the publication data we analyzed was only data from Scopus and the analysis we used used VOSviewer and biblioshiny.